Review of Reactions and Molecular Mechanisms in Cellulose Pyrolysis - Kawamoto, Haruo (Current Organic Chemistry, 2016)
Cellulose, which is a polymer of β-1→4 linked D-glucose units, comprises about half the components of lignocellulosic biomasses. A better understanding of the chemistry involved in cellulose pyrolysis provides valuable insights into the development of efficient pyrolysis-based conversion technologies of biomass into biofuels, biochemicals and biomaterials. This review focuses on the reactions and molecular mechanisms that determine the reactivity and product selectivity in pyrolysis and the related conversion technologies. This information is useful for understanding the processing technologies conducted at high temperatures, such as wood drying and the production of cellulose-plastic composite materials. Because the cellulose pyrolysis behavior changes drastically in the temperature range of 300–350 °C, this review is divided into low- and high-temperature regimes. The intermediates produced from cellulose pyrolysis are further converted into various gas, liquid or solid products. Hence, these processes are addressed as primary pyrolysis and secondary reactions in this review. The roles of the crystalline cellulose in pyrolysis are noted.
Keywords: controlled pyrolysis